26th International Symposium on Ballistics, Miami, Florida 12-16 September 2011 [electronic resource] - International symposium on ballistics (26th : 2011 : Miami, FL); Baker, Ernest, editor; Templeton, Douglas, editor (Pennsylvainia : DEStech Publications, Inc., 2011)
Includes bibliographical references and index